Why do some new products fail? Evidence from the entry and exit of Vanilla Coke - Robert Clark; Yiran Gong (Queen's University, Department of Economics, 2021)
The analysis of new product introduction using discrete-choice demand models has focused on successful products (e.g. the minivan) and their welfare impacts. Instead, we apply this approach to unsuccessful products to provide insight into the reasons for their failure. Our case study is the introduction and subsequent exit of Coca Cola's Vanilla Coke. Using IRI scanner data we estimate demand and supply and simulate counterfactual scenarios in which Vanilla Coke was not introduced. We then estimate Coca Cola's profit gains from the new brand and find they would not cover fixed costs. We analyze the importance of (i) overall demand for soft drinks, (ii) private label presence, (iii) rival promotion, and (iv) consumer preferences for explaining Vanilla Coke's failure, by investigating what the levels of each would have had to be for Vanilla Coke to at least cover its fixed costs. We then investigate the extent to which Coca Cola may have misjudged the levels for these variables by looking at their pre-introduction values. We find Coca Cola did anticipate part of rival reactions that made survival harder, but the actual changes were even beyond its anticipation and contributed to Vanilla Coke's exit.
Keywords: L11; L13; L66; M31; M11; 330; New product introduction; Product Failure; Brand Value; Cannibalization; Soft drink industry